Gut microbiota and the “gut-liver-kidney axis” theory: from mechanisms to therapeutics - Fei, Dai-Liang; Liu, Ying; Liu, Jia; Yu, Ze; Dong, Jin-Liang (Frontiers in Microbiology, 2025)
The gut microbiota is essential for overall health, and in recent years, there has been increasing interest in its complex relationship with the “gut-liver-kidney axis.” In this research, we aim to examine how the gut microbiota affects metabolic and immune responses via influencing the functions of the liver and kidneys. It will also analyze potential pathological mechanisms involved in this interaction and discuss therapeutic strategies that focus on modulating the gut microbiota. Through thoroughly reviewing existing literature, this article intends to offer fresh perspectives and insights that could inform future research and clinical applications in this rapidly developing area of study.